Gastropericardial fistula: a case report - Wójcik, Janusz; Grodzki, Tomasz; Kubisa, Bartosz; Pieróg, Jarosław; Kozak, Anna; Wójcik, Norbert (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
We present a case of a 60-year-old patient with sepsis symptoms and intrathoracic pain lasting 7 hours. Chest X-ray, water soluble-contrast study, computed tomography and gastroscopy revealed infiltration of the fundus of the stomach with radiological features of the gastropericardial fistula. It was decided to perform emergency surgery. Intraoperatively extensive infiltration of the cardia, fundus of the stomach, surroundings of the celiac trunk, splenic hilum, perihiatal part of the diaphragm and pericardium with fistula was found. Because of no possibility to perform intraoperative frozen section and due to technical circumstances, the Ivor-Lewis cardia resection according to oncological protocol with splenectomy, diaphragmatic and pericardial infiltration resection with lymphadenectomy were performed. Intraoperatively pericardial empyema with Escherichia coli and Candida albicans as a type of culture was confirmed. Reconstruction and fenestration of the pericardium was preceded by intensive lavage with Betadine solution. The postoperative course was uncomplicated and the patient was discharged home taking chemoprophylaxis and vaccination against capsular bacteria.